From challenges to assets: Collaborative autoethnography on the transcultural journeys as teacher educators - Han, Seunghoon; Su, Chen; Qi, Yue (Journal of International Students, 2025)
Our study explores the transcultural journeys of three doctoral students from South Korea and China, examining how our diverse experiences as teacher educators in the United States have shaped our teaching practices. Utilizing collaborative autoethnography grounded in transcultural and poststructural theoretical frameworks, we highlight the challenges, growth, and identity (re)formation encountered within the teacher education context. Our findings emphasize the importance of an asset-based mindset in teacher education, advocating for dynamic and inclusive approaches that leverage the rich, multifaceted identities of both teachers and students to foster more equitable educational environments.